2001
DOI: 10.1002/sim.734
|View full text |Cite
|
Sign up to set email alerts
|

Sample size recalculation using conditional power

Abstract: The sample size required to achieve a given power at a prespecified absolute difference in mean response may depend on one or more nuisance parameters, which are usually unknown. Proposed methods for using an internal pilot to recalculate the sample size using estimates of these parameters have been well studied. Most of these methods ignore the fact that data on the parameter of interest from within this internal pilot will contribute towards the value of the final test statistic. We propose a method which in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
86
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(86 citation statements)
references
References 21 publications
(27 reference statements)
0
86
0
Order By: Relevance
“…But, if the unexpected occurs, adaptive methods are available to deal with this. The approach based on maintaining conditional type I error probability put forward by Denne (2001) and by Müller & Schäfer (2001) is particularly promising as it has the potential to be used with error spending designs that already adapt to unpredictable information sequences and, possibly, update sample size in response to estimates of a nuisance parameter.…”
Section: Discussionmentioning
confidence: 99%
“…But, if the unexpected occurs, adaptive methods are available to deal with this. The approach based on maintaining conditional type I error probability put forward by Denne (2001) and by Müller & Schäfer (2001) is particularly promising as it has the potential to be used with error spending designs that already adapt to unpredictable information sequences and, possibly, update sample size in response to estimates of a nuisance parameter.…”
Section: Discussionmentioning
confidence: 99%
“…The interim analysis aimed to evaluate the feasibility of the study with a futility guideline, and possible sample size adjustment, as well, based on the conditional power at the interim mark. 11 The conditional power is the probability of observing a statistically significant treatment effect at the end of a trial, conditional on the data observed at interim and under specific assumptions on the true treatment trends for the remaining 50% patients to be enrolled. A conditional power Ͻ40% at interim was the cutoff at which the DSMB could recommend stopping the study for futility.…”
Section: Data Managementmentioning
confidence: 99%
“…As several authors have pointed out, it is good practice to design a study as efficiently as possible given initial assumptions, so the benefits of this design are obtained in the usual circumstances where no mid-course change is required. However, if the unexpected occurs, adaptations can be made following the methods described in Section 8 or, more generally, by maintaining the conditional Type I error probability, as suggested by Denne(2001) and Müller and Schäfer (2001). Finally, the use of flexible adaptive methods to rescue an under-powered study should not be overlooked: while it is easy to be critical of a poor initial choice of sample size, it would be naive to think that such problems will cease to arise.…”
Section: Discussionmentioning
confidence: 99%